OPTIMIZING SELF-SERVICE TECHNOLOGY TO DRIVE CUSTOMER LOYALTY THROUGH SATISFACTION IN BANDAR LAMPUNG - Syauqi Azizi; Wahyu Dwi Agung Priyo (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
The digital transformation of the banking sector has significantly reshaped customer interactions, particularly in Islamic financial institutions that must integrate technological innovation with Sharia compliance. In Indonesia, Bank Syariah Indonesia (BSI) has introduced digital platforms such as BSI Mobile and BYOND by BSI to enhance service efficiency and accessibility. Nevertheless, customer satisfaction and loyalty toward these platforms remain inconsistent. This study examines the effects of Self-Service Technology (SST), Perceived Value, and Perceived Risk on Customer Loyalty, with Customer Satisfaction serving as a mediating variable among users of BSI Mobile or BYOND by BSI in Bandar Lampung. A quantitative approach was employed using survey data from 150 respondents, analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings indicate that SST has a positive and significant effect on both customer satisfaction and loyalty. In contrast, perceived value and perceived risk do not significantly influence satisfaction or loyalty. Additionally, customer satisfaction significantly mediates the relationship between SST and customer loyalty. These results highlight the critical role of digital service quality in fostering customer satisfaction and sustaining loyalty in Islamic digital banking. The study suggests that BSI should prioritize improvements in system reliability, security, and user experience to strengthen long-term customer relationships.